2006
DOI: 10.3892/or.16.3.497
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of GSTT1-null genotype in predicting toxicity associated to 5-fluouracil irinotecan and leucovorin regimen in advanced stage colorectal cancer patients

Abstract: Abstract.Our aim was to evaluate the role of C-69T in GSTA1, Ile105Val in GSTP1, null allele in GSTT1 and GSTM1 in the prediction of toxicity in patients treated with 5-Fu/CPT-11/Lv regimens in metastatic CRC patients. Fiftyone patients with CRC metastatic disease were analysed. All patients had bidimensionally measurable disease according to WHO criteria. The gender distribution was 37 (74%) males and 13 (26%) females; age ranged from 41 to 71 years; performance status was in all patients ≥80 (Karnofsky index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 22 A few studies find a correlation between UGT1A1 * 28 and diarrhoea 9 , 17 , 23 , 24 or severe toxicity in general, 24 , 25 whereas others find no correlation with toxicity at all. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“… 22 A few studies find a correlation between UGT1A1 * 28 and diarrhoea 9 , 17 , 23 , 24 or severe toxicity in general, 24 , 25 whereas others find no correlation with toxicity at all. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer has been divided into different molecular subtypes based on gene expression profiling. The success of PK dose adjustment is likely to vary by molecular subtype as an association between genotypes and outcomes could be shown [ 56 58 ]. With increasing use of genetic profiling, certain cohorts may be defined who would benefit more from PK testing.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that the null allele in GSTT1 gene might be considered as a new marker when the treatment schedule is administered to metastatic colorectal cancer patients. Besides, the other polymorphisms analysed in that study did not refer to toxicity [ 72 ]. In addition, the neurotoxicity of patients with advanced colorectal cancer treated with a chemotherapy of 5-FU, oxaliplatin and folinic acid was reported to be significantly associated with the 105Ile/Val polymorphism in GSTP1.…”
Section: Polymorphisms Of Glutathione S-transferasementioning
confidence: 99%